Uniaxial pressure effects, phase diagram, and tricritical point in the centrosymmetric skyrmion lattice magnet GdRu2⁢Si2 - Gries, Lukas; Kleinbeck, T.; Mayoh, D. A.; Wood, G. D. A.; Balakrishnan, G.; Klingeler, Rüdiger (Physical review, 2025)
The magnetic phase diagram, magnetoelastic coupling, and uniaxial pressure effects of centrosymmetric magnetic skyrmion-hosting GdRu2⁢Si2 are investigated by means of high-resolution capacitance dilatometry in fields up to 15 T supported by specific-heat and magnetization studies. In addition to the previously reported phases in the 𝐻−𝑇 phase diagram, we observe a third antiferromagnetic phase in zero magnetic field. We present the magnetic phase diagram and find two unreported phases, one of which features a comparably giant uniaxial pressure dependence. Our dilatometric measurements show magnetoelastic effects associated with the various magnetic ordering phenomena. We determine the uniaxial pressure dependencies of the various phases, in particular of the skyrmion lattice phase which is enhanced at higher fields and temperatures and also widens at a rate of 0.07 T/GPa when uniaxial pressure is applied along the 𝑐 axis. The relevance of fluctuations is further highlighted by the presence of a tricritical point indicated by our thermodynamic data at the phase boundary separating two double-𝑄 magnetic configurations between which the skyrmion pocket phase evolves upon further cooling.